BRIDGING TOGETHER AUTHORITARIAN RIGHT-WING POLITICS AND NEOLIBERAL URBAN POLITICS: ISTANBUL’S BID FOR 2020 SUMMER OLYMPICS - YAVUZ, YAVUZ (Society Register, 2021)
This study aims to analyse the political impact of sports mega-events through urban lenses. Sports mega-events often come along with drastic transformations in the built environment of the city where they are held. Contemporary urban impact of the sports mega-events, with the increased role rested by local and/or national governments on the private sector in the organization, is highly interconnected with the neoliberal measures of selling out the urban space, undertaken for hosting the event. In terms of the hosts, there is an increasing shift towards the countries where right-wing authoritarian parties are in power. I argue that the promises of these governments guaranteeing more swift urban transformations to meet the infrastructure requirements of hosting these events cause this shift and in turn, right-wing authoritarian governments use these events as platforms for disseminating their ideologies. This research aims to trace this trend, based on the example of İstanbul’s failed bid to host the 2020 Summer Olympics and the neoliberal urban policies in Turkey under the Justice and Development Party (AKP). By using the city master plan presented during the bidding process and the statements made by AKP officials, I aim to demonstrate how hosting international sports events in Turkey is undertaken as part of a neoliberal urban policy and how this is incorporated into a wider conservative-Islamist political project by the AKP.